Building standard-based nursing information systems (PAHO WashingtonUS, 2001)
Provides a basic source of facts related to the use and implementation of standards in nursing and administrative documentation. Focuses on key issues of modern nursing practice and illustrates how information technology support to the implementation and use of standard-based practice can improve clerical and management nursing functions.
Bibliography: p. 129-135